Wasta as Hybrid Socio-Cultural Capital: Negotiating Legitimacy and Merit in the Digital Gulf - Abu Zummarova, Adriana; Kokaisl, Petr (Anaquel de Estudios Árabes, 2026)
This article examines how wāsiṭa (Arabic: واسطة ), the use of personal connections to gain access to opportunities, is negotiated in digital forums across the Gulf region. Moving beyond traditional definitions of nepotism, we theorize wāsiṭa as a form of hybrid sociocultural capital that blends social ties with cultural legitimacy and moral obligation. Using a hermeneutic approach combined with Latent Dirichlet Allocation (LDA) topic modelling, we analyse 811 comments from platforms including Reddit, YouTube, Instagram, and Saudi university forums. The findings reveal a constitutive moral ambivalence where online users simultaneously condemn the practice as a corrosive barrier to meritocracy while defending it as a pragmatic tool for navigating institutional gaps. We identify three primary interpretive clusters, including pragmatic navigation, moral ambivalence, and structural entrenchment, that illustrate how informal institutions adapt rather than disappear under conditions of modernization. By mapping this digital moral grammar, the study contributes to broader debates on the resilience of informal governance and the shifting nature of legitimacy in contemporary Gulf societies.